Sol-gel derived lead zirconate titanate thick films and their improved pyroelectric properties - Zhang, Qi; Shaw, Christopher P.; Huang, Zhaorong; Whatmore, Roger W. (Taylor and Francis, 2004)
The single-layer thickness of Pb(Zr0.3Ti0.7)O3(PZT 30/70) thin films made by the sol-gel process is often restricted by the appearance of cracks when a single layer is thicker than 100 nm. Making a film with 1μm thick needs more than 10 times coating cycles, which is sometimes unacceptable. In this study, a sol modified with an additive was used for the preparation of thick PZT films. The thickness of the films depends upon the rotation rate. Up to 700 nm crack-free single layers could be obtained. The deposited films crystallised as the perovskite structure on platinum-buffered silicon by heating at 550°C. The porosity of the thick films was a function of the single layer thickness. A dense PZT film with a single layer 140 nm thick was found to have a very high pyroelectric coefficient (p=2.36×10− 4CK− 1m− 2) and figure of merit (1.88×10− 5Pa− 0.5). The introduction of pores in the films reduced p. However, the figure of merit of the films exhibited a reasonably high value due to a dramatic reduction of dielectric constant.